المقامات والأحوال عند الصوفية‪ - حسن، محمد بحر محمد (جامعة إفريقيا العالمية - كلية الشريعة والقانون وكلية الدراسات الإسلامية, 2013)
إن بحث: المقامات والأحوال عند الصوفية، هدف لبيان الفرق بين المقام، والحال. \\\\ فبين أن المقام يقصد به مقام العبد بين يدي الله –تعالى-فيما يقام فيه من العبادات والمجاهدات والرياضات. أما الحال فيقصد به ما يحل بالقلوب، أو تحل القلوب به من صفاء نفسي واطمئنان قلبي، وراحة ذهنية، سببها التقرب إلى الله –تعالى-بالأذكار المشروعة. \\\\ تناول الباحث بعض المقامات مثل: مقام التوبة، والورع والزهد، والفقر، والصبر، والتوكل، والرضا. ومن الأحوال: حال المحبة، والخوف، والرجاء. ووضح أن من التزم الكتاب والسنة في أدائه للمقامات والأحوال فهو صوفي سني، لأنه يزن أفعاله وأقواله بمعيار الكتاب والسنة. وبهذا يفرق بين أنواع التصوف المختلفة. وبهذا المعيار ترد المعاني النفسية والأخلاقية، والسلوكية الناتجة عن المقامات والأحوال إلى القرآن الكريم، والسنة النبوية الشريفة.‪ The research’s aim to show the difference between (Stances) and (Statuses) in the Sufist terminology, explaining that a (stance: magma) is the kind of relation between the worshipper and his god- almighty Allah, while prancing worship, strife (against the devil and are deceives and spiritual exercise, while a (status: hal). \\\\ One of the heart’s different moods, such as mental clarity, heart tranquility, mind relaxation: all of these resulting from nearness to Allah, through remembrance of Allah within the Sharia leaching. \\\\ The researcher discussed some of the stances such as the stances of repentance, god-fearing, asceticism, poverty, patience, dependence and satisfaction, and also discussed some statuses, such as love, fear, and hope. \\\\ The researcher explained that he who a hares to the Quran and tradition in his practice of magams and hals sunni Sufist because his actions and utterances are governed by the Quranic and Sunna norms. \\\\ In this way, the researcher differentiates between the different kinds of Sufism, thereby referring the psychological, ethnical and behavioral in canings resulting from magams and hals to the Quran and Sunnah.
Keywords: التصوف الإسلامى‪ -- الصوفية‪ -- المقامات‪